Analysis Of The Contribution Of Agricultural Subcategories To The Regional Economy Of Kerinci Regency - Fitri, Yanuar; Effran, Endy; Gratia Rumahorbo, Sola (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
Regional economic development required the identification of potential sectors as a basis for policy formulation. This study aimed to: 1) describe the condition of agricultural subcategories in Kerinci Regency; 2) analyze agricultural subcategories as base or non-base sectors; and 3) analyze the role of agricultural subcategories in the regional economy based on the Gross Regional Domestic Product aspect. The research was conducted in Kerinci Regency, with Jambi Province serving as the reference region. The data used were Gross Regional Domestic Product at constant prices (2010 base year) for the period 2014–2023, which were analyzed using Location Quotient, Dynamic Location Quotient, and Shift-Share analysis. The results showed that agricultural subcategories were the largest contributors to the agriculture, forestry, and fisheries category, accounting for 97.31%, and contributed 44.8% to the total Gross Regional Domestic Product. The Location Quotient analysis indicated that agricultural subcategories were base sectors, with food crops, horticulture, livestock, and agricultural services and hunting classified as base sectors, while plantations were categorized as non-base. The Dynamic Location Quotient analysis showed that agricultural subcategories were projected to become non-base sectors in the future. Meanwhile, the Shift-Share analysis identified horticulture as the only sub-subcategory that experienced competitive growth, while other sub-subcategories exhibited relatively slow growth within the agricultural subcategory. These findings confirmed that the agricultural sector had significant potential and required improvements in productivity, intensification strategies, and the provision of sustainable agricultural land to strengthen its role.